Influence of mineral substances on the synthesis of volatile organic compounds by Pleurotus ostreatus in the process of solid phase cultivation - E. N. Vlasenko (Regulatory Mechanisms in Biosystems, 2017)
Mineral substances play an important role in ensuring high-grade growth and high organoleptic quality of the fruit bodies of basidiomycetes. In the process of solid-phase cultivation of the mushroom Pleurotus ostreatus (Jacq.: Fr.) Kumm. the lignocellulosic substrates were enriched with mineral additives of calcium, iron and selenium. Their influence on the synthesis of volatile aroma compounds was investigated by the methods of sensory profile analysis and ultraviolet spectroscopy. Mineral additives in the form of CaCl2, FeSO2•7H2O and Na2SeO3 salts were added to the substrate (sunflower husk, barley straw) before sterilization in concentrations that correspond to the physiological needs of the mushrooms. When carrying out a sensory profile analysis of dried fruit bodies, the following attributes of the flavor were determined: mushroom, woody, sweet, herbaceous, fish, meat, floral, earthy, acidic, putrescent. The conducted profile analysis showed an unequal dependence of the effect of mineral additives for each of the P. ostreatus strains. For IBK-549 and IBK-1535, an increase in the intensity of mushroom notes of aroma was observed with the addition of calcium and selenium to the husks, and for IBK-551, this was observed with the addition of iron and selenium to both substrates. The volatile aroma compounds were extracted with hexane at boiling point for 30 minutes. Absorption spectra were recorded in the wavelength range 200–330 nm. The examined extracts had light absorption maxima at 200–210 and 260–300 nm, which is typical for solutions of unsaturated compounds that have non-conjugated double bonds, saturated and unsaturated aldehydes and ketones. Additions of iron to the substrates increased the intensity of light absorption in comparison with the control. Additions of selenium selectively influenced different strains, and calcium ions did not significantly affect the change in the intensity of light absorption, and therefore the synthesis of volatile compounds by mushrooms. The level of synthesis of aroma-forming substances was higher when cultivating fungi on sunflower husks than on barley straw. This was confirmed both by the obtained aroma profiles and by the recorded absorption spectra of all examined strains. The study showed the possibility of influencing the organoleptic qualities of P. ostreatus fruiting bodies during solid-phase cultivation by supplementing the composition of lignocellulosic substrates with various mineral additives.